Distribution and community structure of tropical gastropod in the intertidal area of Bintulu, Borneo - Hamli, Hadi; Yusof, Muhammad Hafiy; Idris, Mohd Hanafi (Malaysian Society of Applied Biology, 2024)
Marine gastropods can be considered a biological indicator of the ecosystem's health, such as intertidal areas. The objectives of this study are to identify marine gastropod species, diversity, and distribution along the coastal area of the Bintulu Division. The study was conducted in December 2021. A 50 m transect was laid perpendicular to the coastal line, and three quadrats were set up at each transect at all four stations. The specimen of gastropod were counted and collected from each sampling station, then preserved in ice and taken to the laboratory for the species identification. The gastropods subject to an analysis for their diversity index and morphological characteristics. Forty-three species of marine gastropods were discovered, representing 25 families and 39 genera. The, Shannon-Weiner diversity index (H’), evenness index (J’) and Simpson index (1-D) index were assessed, whereas the station 4 indicated higher diversity of Gastropods followed by stations 3,2 and 1. The dominance index (D) showed an inverse relationship, with the highest value observed at station 1, followed by stations 2, 3, and 4.The information presented in this paper might be helpful for ecological wealth studies and considered as the baseline data for the intertidal ecosystem in Sarawak, Malaysia.